KURVA INTENSITY DURATION FREQUENCY CURAH HUJAN UNTUK KOTA PAGAR ALAM - Azizah, Barrorotul; Dhiniati, Fameira ((JITEK)Jurnal Ilmiah Teknosains, 2025)
This study aims to build an Intensity Duration Frequency (IDF) curve of rainfall in Pagar Alam City that can be used as a reference for civil engineering planning, such as drainage and flood control. Daily rainfall data from PTPN VII Pagar Alam Station for 10 years were analyzed using the Gumbel method for calculating the return period. Rain intensity was calculated based on the duration of rain of 5, 10, 15, 30, 60, 120 and 180 minutes. The results showed that rainfall intensity increased with increasing return period and decreased with increasing rain duration. The IDF curve equation was obtained for various return periods (2, 5, 10 years) which were formulated in mathematical form. This IDF curve model can be used by planners in calculating the design discharge for urban drainage system needs in Pagar Alam City